2002
DOI: 10.1345/aph.1a152
|View full text |Cite
|
Sign up to set email alerts
|

Brasofensine Treatment for Parkinson's Disease in Combination with Levodopa/Carbidopa

Abstract: Brasofensine was safe and well tolerated in the patient cohort studied at daily doses of up to 4 mg. Adverse events were generally mild in intensity, and included headache, insomnia, phlebitis, dizziness, ecchymosis, and vomiting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…Thus, the primary role of brasofensine is to conserve the greatly reduced level of endogenous dopamine within the synaptic cleft and also to extend the potency and duration of action of exogenous dopamine from the administration of levodopa. This appears to be true in a marmoset model of Parkinson's disease (Pearce et al, 2002) but has not yet been shown in the clinic (Frackiewicz et al, 2002).…”
mentioning
confidence: 88%
“…Thus, the primary role of brasofensine is to conserve the greatly reduced level of endogenous dopamine within the synaptic cleft and also to extend the potency and duration of action of exogenous dopamine from the administration of levodopa. This appears to be true in a marmoset model of Parkinson's disease (Pearce et al, 2002) but has not yet been shown in the clinic (Frackiewicz et al, 2002).…”
mentioning
confidence: 88%
“…In a small escalating-dose study, brasofensine did not enhance L-DOPA antiparkinsonian action and did not alter L-DOPA-induced dyskinesia severity (Archibald, 2000;Cutler et al, 2000;Frackiewicz et al, 2002). In a phase II trial, the administration of brasofensine as monotherapy to patients with recently diagnosed PD initially improved parkinsonism, but the improvement was not maintained after 2 weeks (Yu, 2000).…”
Section: Dual Dat and Nat Inhibitorsmentioning
confidence: 99%
“…It seems likely that they have potential to supply antiparkinsonian benefits as monotherapy and in some situations, at least, can enhance L-DOPA benefits, although this might be at the expense of exacerbating dyskinesia. Interestingly, methylphenidate improved speed of movement without extending on-time duration, suggesting that dual DAT/NAT inhibitors (Singh, 2000) Undisclosed None Antiparkinsonian action as monotherapy (Pearce et al, 1995) No effect on L-DOPA antiparkinsonian action (Archibald, 2000;Cutler et al, 2000;Frackiewicz et al, 2002) Does not elicit dyskinesia as monotherapy (Pearce et al, 1995) No effect on L-DOPA-induced dyskinesia severity (Archibald, 2000;Cutler et al, 2000;Frackiewicz et al, 2002) Enhances the antiparkinsonian action of low-dose L-DOPA (Moldt et al, 1998;Pearce et al, 2002) Transient antiparkinsonian benefit as monotherapy (Yu, 2000) Not tested in combination with high-dose L-DOPA in primed, dyskinetic parkinsonian monkeys BTS-74,398 DAT = NAT = SERT (Cheetham et al, 1998) Undisclosed None Antiparkinsonian action as monotherapy (Hansard et al, 2002b(Hansard et al, , 2004 n/a …”
Section: Dual Dat and Nat Inhibitorsmentioning
confidence: 99%
“…For example, a new class of drugs (monoamine uptake inhibitors) that had produced promising results in MPTP-treated nonhuman primate models resulted in only a very limited level of functional improvement and a high incidence of side effects when tested in humans for the first time. 39 In this way, inconsistencies between animal models of Parkinson's disease and the human condition make it particularly difficult to accurately predict both the potential risks and the potential efficacy during first-in-human trials.…”
Section: The Translational Gap: Moving From Bench and Beast To Bedsidementioning
confidence: 99%